Clinical outcomes of arthroscopic suprascapular nerve decompression for suprascapular neuropathy - Nolte, Philip-Christian; Woolson, Thomas E.; Elrick, Bryant P.; Nolte, Anna-Katharina; Horan, Marilee P.; Godin, Jonathan A.; Millett, Peter J. (Arthroscopy, 2021)
Purpose - To report clinical outcomes following arthroscopic suprascapular nerve (SSN) decompression for suprascapular neuropathy at the suprascapular and/or spinoglenoid notch in the absence of major concomitant pathology. - Methods - We retrospectively reviewed prospectively collected data of 19 patients who underwent SSN release at the suprascapular and/or spinoglenoid notch between April 2006 and August 2017 with ≥2 years of follow-up. Patients who underwent concomitant rotator cuff or labral repairs or had severe osteoarthritis were excluded. Pre- and postoperative strength and patient-reported outcomes were collected, including the American Shoulder and Elbow Surgeons (ASES), Single Assessment Numerical Evaluation (SANE), Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH), 12-item Short Form (SF-12), and satisfaction. Complications and revisions were recorded. - Results - At a mean final follow-up of 4.8 years, pre- to postoperative ASES (64.9 ± 18.7 versus 83.5 ± 23.1; P = .018), QuickDASH (28.7 ± 17.2 versus 12.7 ± 17.1; P = .028), SANE (64.3 ± 16.4 versus 80.8 ± 22.3; P = .034), and SF-12 PCS (41.1 ± 10.8 versus 52.3 ± 5.8; P = .007) scores all significantly improved. Median strength for external rotation improved significantly (4 [range 2 to 5] versus 5 [range 3 to 5]; P = .014). There was no statistically significant improvement in median strength for abduction (4 [range 3 to 5] versus 5 [5]; P = .059). Median postoperative satisfaction was 9 (range 1 to 10), with 8 patients (50%) rating satisfaction ≥9. No complications were observed, and no patients went on to revision surgery. - Conclusion - Arthroscopic SSN decompression for suprascapular neuropathy at the suprascapular and/or spinoglenoid notch in the absence of major concomitant glenohumeral pathology results in good functional outcomes with significant improvements from before to after surgery. - Level of Evidence - IV, therapeutic case series.
Gesehen am 12.05.2021
First published: 19 October 2020